(untitled) (LIS TODAY, 2022)
This paper is going to aware in the field of Artificial Intelligence focusing on how it’s applied in the Library world. The concept such as machine learning, deep learning and their various applications by Technique is enumerated. In this paper an attempt has been made to identify the different applications of Artificial Intelligence into the libraries. The various concepts such as expert system, natural language processing, pattern recognition and robotics and their application to the library operation and services have been explained thoroughly. The advantages and disadvantages of Artificial Intelligence have also been discussed.